2017
DOI: 10.1515/aslh-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the Hydrological Balance in the Area of the Kiskunság National Park Directorate

Abstract: -The aim of this paper is to show how hydrological measurements made in forests and grasslands can contribute to the conservation treatment of ecologically significant habitats. The study was carried out in three different forest stands and their surrounding grasslands in the area of the Kiskunság National Park Directorate between 2012 and 2015. Different methods were applied during the research of the water balance. The average values of canopy interception were 23% in the Scots pine stand and 19.2% in the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
1
2
0
2
Order By: Relevance
“…The reason for the conflicting results is that the water table dropped from 3-5 meters to almost 10 meters during the last couple of decades and the vegetation root systems could not adapt to this drastic decrease. This is corroborated by the results of other authors indicating that the maximum root depths are around 3.3 m based on the available direct and indirect data of the studied tree species (Bolla and Németh 2017;Kárász, 1986;Móricz et al 2016;Musters and Bouten,1999;Tóth et al, 2014).…”
Section: Results Groundwatersupporting
confidence: 90%
See 2 more Smart Citations
“…The reason for the conflicting results is that the water table dropped from 3-5 meters to almost 10 meters during the last couple of decades and the vegetation root systems could not adapt to this drastic decrease. This is corroborated by the results of other authors indicating that the maximum root depths are around 3.3 m based on the available direct and indirect data of the studied tree species (Bolla and Németh 2017;Kárász, 1986;Móricz et al 2016;Musters and Bouten,1999;Tóth et al, 2014).…”
Section: Results Groundwatersupporting
confidence: 90%
“…Thus it was concluded that the water uptake of the forests is currently restricted to the unsaturated zone. This is due to the water table depth and the relatively shallow root system of the examined two tree species as Kárász (1986) found, that in the case of black locust, the bulk of the root system is in the upper 30 cm of the soil with some roots reaching the depth of 3 m. The diurnal cycles under the black locust were found at the maximum depth of 3.1 m by Móricz et al (2016), 3.2 m by Tóth et al (2014), and 2.5 m by Bolla and Németh (2017). Similar root zone depths (from 0.8 to 3.3 m) were measured by Musters and Bouten (1999) and Stokes et al (2002) under black pine.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Hazánkban az ERTI talajvízmonitoring kúthálózatában (IJJÁSZ 1939) VITUKI Komlósi telep nevű kísérleti állomásán folytattak intenzív vizsgálatokat az evapotranszspiráció talajvízre gyakorolt hatását tanulmányozva (MAJOR 2002). Érdemes megemlíteni a TAKI (TÓTH et al 2014) az SOE Erdőmérnöki Kara (GRIBOVSZKI et al 2008 és az Erdészeti Tudományos Intézet talajvízzel kapcsolatos elemzéseit is (JÁRÓ-SITKEY 1995, MÓRICZ et al 2016, BOLLA-NÉMETH 2017, SZABÓ et al 2022, amelynek kapcsán különböző típusú erdőállományok hatását vizsgálták a talajvízszintekre vonatkozólag.…”
Section: Bevezetésunclassified
“…Eme kutatási eredmények publikálása a vezető nemzetközi szaklapokban is lehetővé vált. A módszert számos vizsgálati ponton, eltérő körülmények között sikeresen alkalmazták elsősorban erdőállományok talajvízfelvételének becslésére (Móricz et al 2012;Tóth et al 2014;Csáfordi et al 2017;Bolla és Németh 2017).…”
Section: Transzspirációunclassified